Arthropod predators of Dalbulus maidis (Hemiptera: Cicadellidae) in northern Argentina, including data on the species registered in all the Americas - Casuso, Violeta Macarena; Melo, María C.; Maza, Noelia; Rios-Tamayo, Duniesky; Reguilón, Carmen; Bezdjian, Laura Patricia; Virla, Eduardo Gabriel (Wiley, 2025)
In most tropical and subtropical regions of the Americas, the corn leafhopper, Dalbulus maidis (DeLong & Wolcott)(Hemiptera: Cicadellidae), is a significant pest of corn. Crop losses occur not only due to direct damage from feeding and oviposition but also because this leafhopper is vector of various pathogens causing important outbreaks of the corn stunt disease. While parasitoids are the better-studied natural enemies of this leafhopper, its predators remain largely unknown. This study records, for the first time, 26 predator species [14 spiders, three lacewings (Chrysopidae), two assassin bugs (Reduviidae), one big-eyed bug (Geocoridae), one hoverfly (Syrphidae), four ladybugs (Coccinellidae) and two pincer wasps (Dryinidae)] as active predators of the vector in cornfields of northern Argentina. These records, along with the three previously known species, form a complex of 29 species preying on different stages of the vector in Argentina. With this contribution, 40 species of predators are now documented across the Americas, providing a valuable natural resource that should be conserved.